Validity and Reliability Test of Badminton Smash Accuracy - Eval Edmizal; Eri Barlian; Donie Donie (Journal of Educational and Learning Studies, 2022)
An instrument must be verified for validity and dependability to produce accurate research data for conclusions based on actual circumstances. This investigation seeks to establish the validity and reliability of badminton smash accuracy. The population of this study was thirty respondents. The sampling method employed purposive sampling with a sample size of 24 respondents. Data collection of smash accuracy using the Shaleh Anasir smash accuracy test, testing the validity of smash accuracy by correlating the results of the Shaleh Anasir smash accuracy test with the developed smash accuracy test, and testing the reliability of smash accuracy by linking the results of the first test and the second test of smash accuracy. Based on the collected data analysis, the level of validity of badminton smash accuracy is 0.84, which is excellent, while the level of reliability of the smash accuracy test is 0.78, which is acceptable